The Effect of Insecticide Endrin on Soybean Root Nodules Bacteria Rhizobium japonicum - U. Suriawiria (Institute for Research and Community Services (LPPM) ITB, 1974)
Abstract. The effects of Endrin on soybean root nodules baccteria Rhizobium japonicum has been studied. In pot experiments with soybean and addition of Endrin gave no quantitative change of these bacteria during any part of the vegetation period, Rhizobium japonicum strains have been isolated from Endrin treated soil. These cultures grew fairly well in medium with Endrin as the sole source of carbon. Ringkasan. Telah diselidiki pengaruh insektisida Endrin terhadap bakteri nodula akar kacang kedele Rhizobium japonicum. Ternyata dalam percobaan dengan menggunakan pot yang disertai penambahan Endrin, tidak memberikan perubahan jumlah dari bakteri tersebut selama pertumbuhan kacang kedele. Strains Rhizobium japonicum dapat dipisahkan dari tanah-tanah yang diberi perlakuan Endrin. Biakan-biakan dari bakteri tersebut tumbuh baik pada media yang diberi penambahan Endrin sebagai sumber C.